BRANCH RETINAL ARTERY OCCLUSION ASSOCIATED WITH PARACENTRAL ACUTE MIDDLE MACULOPATHY IN A PATIENT WITH LIVEDO RETICULARIS. Issue Volume 11:Issues 4(2017:Autumn) (2017) - Baciu, Paul; Nofar, Candice M.; Spaulding, Justin; Gao, Hua
Abstract : Purpose: To report the occurrence of a branch retinal artery occlusion with paracentral acute middle maculopathy in an otherwise healthy young man with a history of livedo reticularis (LR). Methods: Retrospective case report. Patients: A 21-year-old man with a history of LR being treated with pentoxifylline developed an acute branch retinal artery occlusion with initial best-corrected visual acuity at presentation of 20/80. Results: A thorough diagnostic work up was negative for potential causes of branch retinal artery occlusion or LR. The patient was continued on pentoxifylline and started on aspirin 81 mg daily. At five-month follow-up, vision had improved to 20/25. Optical coherence tomography testing showed a hyperreflective band in the inner nuclear layer and outer plexiform layers in the affected eye that ultimately thinned, consistent with paracentral acute middle maculopathy. Conclusion: To our knowledge, this is the first case of branch retinal artery occlusion occurring in a patient with a history of LR. This could potentially be an early manifestation of Sneddon syndrome, a rare entity characterized by LR and cerebrovascular disease, which has been previously associated with central retinal artery occlusions. Abstract : The authors report the case of a 21-year-old man with a history of livedo reticularis presenting with an acute branch retinal artery occlusion. He was being treated with pentoxifylline at the time of presentation, and vision gradually improved with continued pentoxifylline use and addition of daily aspirin.